2021
DOI: 10.1016/j.acra.2020.11.001
|View full text |Cite
|
Sign up to set email alerts
|

18FDG-PET/CT Assessment of COVID-19-Induced Bell's Palsy

Abstract: Dear Editor-While fever, cough, and dyspnea are the main symptoms of coronavirus disease-2019 (COVID-19), nonrespiratory presentations have been increasingly recognized, including neurological manifestations (1-3). Herein, we describe the first report of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-induced facial nerve palsy assessed by 18 fluoro-2-deoxy-d-glucose (18 FDG) positron emission tomography-computed tomography (PET/CT). A 60-year-old healthy man with COVID-19, confirmed by polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Other focal signs preliminarily investigated by 18 F-FDG PET include a case of facial palsy with putative hypometabolism of the respective facial nerve ( 34 ) and a patient with frequent focal seizures possibly due to subacute encephalitis after SARS-CoV-2 infection with a normal 18 F-FDG PET result ( 35 ) (Supplemental Table 1). Another group reported hypermetabolism of the inferior colliculi as a novel finding in patients with COVID-19 ( 36,37 ) that was associated with more frequent seizures and higher blood leukocytes at admission.…”
Section: Insights From Molecular Imaging With Pet and Spectmentioning
confidence: 99%
“…Other focal signs preliminarily investigated by 18 F-FDG PET include a case of facial palsy with putative hypometabolism of the respective facial nerve ( 34 ) and a patient with frequent focal seizures possibly due to subacute encephalitis after SARS-CoV-2 infection with a normal 18 F-FDG PET result ( 35 ) (Supplemental Table 1). Another group reported hypermetabolism of the inferior colliculi as a novel finding in patients with COVID-19 ( 36,37 ) that was associated with more frequent seizures and higher blood leukocytes at admission.…”
Section: Insights From Molecular Imaging With Pet and Spectmentioning
confidence: 99%
“…Karimi-Galougahi et al noted decreased metabolic activity in the orbitofrontal cortex associated with the COVID-19 induced anosmia ( Figure 3 ) 32 . In addition, these authors used FDG-PET/CT to investigate COVID-19 induced facial nerve palsy, and FDG-PET/CT findings have also indicated reduced neurological radiotracer uptake in several brain areas prior to symptom onset, during active illness, and 6 months after infection 33 , 34 , 35 . The acute reduction in uptake was primarily found in the pre-frontal cortex, mimicking the patterns of several neurodegenerative disorders 33 , 34 , 35 .…”
Section: Fdg-pet/ct and Extrapulmonary Manifestations Of Covid-19mentioning
confidence: 99%
“…In addition, these authors used FDG-PET/CT to investigate COVID-19 induced facial nerve palsy, and FDG-PET/CT findings have also indicated reduced neurological radiotracer uptake in several brain areas prior to symptom onset, during active illness, and 6 months after infection 33 , 34 , 35 . The acute reduction in uptake was primarily found in the pre-frontal cortex, mimicking the patterns of several neurodegenerative disorders 33 , 34 , 35 . Other authors such as Sollini et al have identified increased FDG uptake in vasculature in those patients complaining of persistent symptoms post-infection 36 .…”
Section: Fdg-pet/ct and Extrapulmonary Manifestations Of Covid-19mentioning
confidence: 99%
“…Using these medications, 20 patients had clinical improvement or recovered completely from FNP, while 1 patient failed to show any recovery [ 11 ]. Additionally, three people were not reported [ 32 , 35 , 36 ]. Specifically, glucocorticoids were recommended for the treatment of Bell’s palsy, but glucocorticoids can be contraindicated in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…This can cause a false sense of precision due to the unknown effects of the defining characteristics on the potential correlation between FNP and COVID-19. Finally, some papers have based the COVID-19 diagnosis on only the clinical findings, serological testing, and/or CT scan findings without the confirmation of a PCR test [ 35 , 41 , 42 ]. This was widely exercised at the beginning of the pandemic due to the scarcity of PCR tests, the overwhelming number of new cases, or the high cost of a PCR test, especially in low-to-middle income countries [ 43 ].…”
Section: Discussionmentioning
confidence: 99%